Teknik Modeling untuk Membentuk Perilaku Menolong dan Sopan Santun Siswa - Nor Fadilah; Asyaari Asyaari; Eva Rosita; Dirga Ayu Lestari (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The research aims to explain and describe modeling techniques, polite behavior, and the impact of modeling techniques on students' helping and polite behavior at Raudhatul Athfal Nurul Hidayah Pemakasan. The research method is qualitative through a case study approach. Data collection techniques include observation, interviews, and documentation. Data processing techniques involve condensation, data presentation, and drawing conclusions. Data validity techniques include credibility. Research findings: (1) Modeling techniques: Attention Stage with student conditioning, attracting students' attention through singing and guessing games, and demonstrating helpful and polite behavior. Retention Stage involves recalling demonstrations and applying behavior. The reproduction Stage involves repeating behavior and giving tasks. The motivation Stage involves giving rewards and punishments. (2) Polite and courteous behavior: students helping each other in small matters, such as completing tasks or providing pencils, also being polite to teachers. (3) Impact: Students start helping each other in small matters, such as completing tasks providing pencils, and being polite to teachers.